Preservation of access? Developing strategies for microfilming and digitisation - Jefcoate, Graham (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
First of all, I should like to thank Maria Luisa Cabral and the organisers of this LIBER workshop for inviting me to give this keynote address. I hardly need an excuse to come to the Hague and to the KB, the National Library of the Netherlands, where, through working with KB colleagues, I have learnt such a lot about the future potential of European libraries over the years. When the invitation was issued last year, I had myself only recently taken charge of a large international research library. As many of you know, I have now left that post at Berlin, so that what I shall be saying today is based on my thinking about some of the issues from the point of view of library decision makers, but I won't be constrained by current institutional responsibility. Needless to say, I shall also be drawing on my personal experience of preservation and digitisation issues not only at Berlin State Library but also at the British Library, latterly as the Head of Early Printed Collections, and especially as it relates to surrogacy or reformatting.